A SURMISE REGARDING THE ORIGIN OF BOOKKEEPING BY DOUBLE ENTRY. - Kats, P. (The Accounting Review, 1930)
Abstract Accounting has long since been recognized as a science indispensable in its application to daily life, so much so that it seems incomprehensible that times have been, and not even very remote in which it did not exist otherwise than in extremely crude forms. Bookkeeping is such an integral part of accounting that, until recently, the words were held to be interchangeable. That is why, in endeavoring to trace the origin of accountancy, one always looks for the earliest manifestations of bookkeeping. Unfortunately, in making such assertions, one does not always duly bear in mind modern notions of bookkeeping, but if to those ancient documents the criterion of modern, representative, definitions may not be applied, confusion is bound to arise and should be obviated by giving different names such as accounting or account-keeping-to those precious relics, mute but eloquent witnesses of the glories of civilizations of the dim past. In this sense, therefore, accounting and bookkeeping are not identical and the latter indicates a state of evolution that was never reached by Sumerian, Egyptian or other such ancient cultures of which the accounting records are available.